Amorphous electrocatalyst Co / MoO2 as well as preparation method and application thereof
By developing the amorphous electrocatalyst Co/MoO2, the advantages of its amorphous structure and metal compounds are used to solve the problems of low efficiency and poor circulation performance of lithium-sulfur battery, and achieve higher circulation stability and rate performance.
Patent Information
- Application Number
- CN202411848778.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-04
AI Technical Summary
Lithium sulfur battery has low efficiency, poor circulation performance, high self-discharge rate, low electronic conductivity, high expansion coefficient, and shuttle effect of soluble polysulfides seriously affect the electrochemical performance.
Amorphous metal oxide electrocatalyst Co/MoO2 was developed, which was prepared by solvent method and high-temperature calcination. It utilizes the advantages of amorphous structure and metal compounds to provide rich active sites and strong polarity, inhibit the shuttle effect of polysulfides, and improve the conductivity through metal bonds.
Effectively inhibit the shuttle effect, promote efficient transformation of sulfur species, accelerate the kinetics of redox reactions, reduce electrode polarization, and improve the cycle stability and rate performance of lithium-sulfur batteries.
Smart Images

Figure CN119764449A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and more specifically, relates to an amorphous electrocatalyst Co / MoO2 and a preparation method and application thereof. Background Art
[0002] Energy is a key driving force for scientific and technological innovation, economic development and social progress. With the rapid development of society, the demand for energy is also increasing, which has led to the long-term over-exploitation of non-renewable resources such as natural gas, coal and oil, causing a profound energy crisis and irreversible environmental pollution. Renewable energy such as geothermal energy, solar energy, wind energy, biomass energy, and hydropower have emerged and attracted people's continuous attention. Among them, metal energy batteries are considered to be one of the most promising technologies to solve energy problems. However, to achieve progress in energy storage, the continuous updating and transformation of materials is essential. Among various materials, amorphous electrocatalysts have become the object of research by scientific researchers in recent years because of their significant advantages. On the one hand, amorphous materials have flexible structures and are isotropic, and can achieve surface and volume confined electrocatalysis at the same time. On the other hand, amorphous electrocatalysts have abundant defects and vacancies, which can provide a large number of active sites to promote the redox reaction of lithium-sulfur batteries.
[0003] In recent years, lithium-sulfur batteries have been widely used due to their high performance of up to 1675 mAh g -1 The theoretical specific energy of sulfur has attracted widespread attention. At the same time, sulfur has the characteristics of abundant reserves, non-toxicity and environmental protection, showing extremely high application potential. However, at the current technological level, lithium-sulfur batteries still face many technical difficulties and shortcomings. These problems are mainly manifested in the low coulombic efficiency, poor cycle performance, and high self-discharge rate of lithium-sulfur batteries. Especially in the general lithium-sulfur battery positive electrode, the low electronic conductivity of sulfur, the high expansion coefficient, and the shuttle effect of soluble polysulfides seriously affect the electrochemical performance of lithium-sulfur batteries.
[0004] Compared with crystalline catalysts, amorphous electrocatalysts can achieve both surface and volume confined electrocatalysis, making the catalytic process more global and three-dimensional, greatly improving the catalytic efficiency, while crystalline catalysts can only perform surface catalysis. Amorphous electrocatalysts often have abundant defects and vacancies, which will produce a large number of dangling bonds, providing a large number of active sites for the reaction and improving the overall catalytic activity. The structure of amorphous materials is flexible and isotropic, allowing active sites to adopt any geometric shape required for the electrocatalytic reaction and facilitating dynamic surface reconstruction, thereby optimizing the surface state. Amorphous electrocatalysts generally have better corrosion resistance because they are easier to self-heal than crystalline electrocatalysts, which is beneficial for the catalyst to continue to play a catalytic role during long-term battery cycling.
[0005] Therefore, there is a need to develop more amorphous metal oxide electrocatalysts for separators for application in lithium-sulfur batteries. Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention discloses an amorphous metal oxide electrocatalyst for use on a diaphragm. From the perspective of promoting the efficient conversion of sulfur species, on the one hand, the unique advantages of the amorphous structure are utilized to simultaneously catalyze from the surface and volume confinement range, and the catalyst itself has abundant vacancies and defects, providing a large number of active sites for the reaction; on the other hand, metal compounds occupy an important position in lithium-sulfur battery catalysts, mainly including metal sulfides, metal oxides, metal nitrogen / carbides, and metal hydroxides. Metal compounds mainly anchor polysulfides through strong chemical interactions of polar bonds. The anions such as nitrogen, carbon, oxygen, sulfur, and hydroxide contained in them have a strong affinity for polysulfides. During the charge and discharge process, polysulfides can be confined to the positive electrode side, effectively inhibiting the shuttling effect of polysulfides. In addition, metal atoms are introduced into this catalyst to produce a large number of metal bonds, which solves the problem of low conductivity inherent in amorphous materials. The present invention combines the advantages of amorphous structures and metal compounds to develop an electrocatalyst with abundant vacancies and defects, strong polarity and strong conductivity. Applying it to lithium-sulfur batteries can effectively inhibit the shuttle effect, promote the efficient conversion of sulfur species, accelerate the kinetics of redox reactions, and reduce electrode polarization, ultimately obtaining a lithium-sulfur battery with stable cycle performance and excellent rate performance.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] An amorphous electrocatalyst Co / MoO2, wherein the amorphous electrocatalyst Co / MoO2 is prepared as follows:
[0009] S1. Obtaining precursor materials by solvent method:
[0010] S11, stirring and dissolving molybdenum salt, ethylenediamine and cobalt salt in water respectively, and then mixing to obtain solution A;
[0011] S12, adding 1M HCl aqueous solution dropwise to solution A until precipitation occurs;
[0012] S13, keeping the entire solution A system warm and then centrifuging it to obtain a precipitate, washing the precipitate, and drying it to obtain material B;
[0013] S2. Preparing a metal oxide composite amorphous material doped with a single metal by high temperature calcination:
[0014] The material B obtained in step S1 is used as a precursor; in an inert gas atmosphere, the precursor B is calcined at 500-600 degrees Celsius in a tube furnace for 1.5-3 hours, and then the product is collected to obtain the product.
[0015] The above design of the present invention is designed as follows: through amorphous design, the coordination number of Mo is reduced to enhance the overall catalytic activity, and metal elements are introduced to generate metal bonds to improve the conductivity of the amorphous catalyst. The synthesized electrocatalyst a-Co / MoO2 presents a rod-like structure as a whole, and there are a large number of pore structures on its surface. XRD (attached) Figure 1 ) and STEM (with Figure 2 ) The results confirmed that it has a typical amorphous structure, which can provide a large number of active sites to promote the transfer of electrons and ions. The application of a-Co / MoO2 not only promotes the efficient conversion of sulfur substances and accelerates the redox kinetics, but also the strong polarity of metal oxides is conducive to anchoring polysulfides on the positive electrode side, effectively inhibiting the shuttle effect. The introduction of Co also produces a large number of Co-Mo metal bonds, which improves the overall conductivity of the catalyst.
[0016] Preferably, the molybdenum salt is ammonium molybdate, and the cobalt salt is cobalt acetate tetrahydrate.
[0017] Preferably, the molar volume concentration ratio of the ammonium molybdate, ethylenediamine and cobalt acetate tetrahydrate is (5-8):(10-30):(0.03-0.2).
[0018] Preferably, the concentration of ammonium molybdate in solution A is 0.05-0.1 g / ml.
[0019] Preferably, the stirring in step S1 is performed at a rotation speed of 200 to 400 rpm.
[0020] Preferably, the step S13 is to keep the entire solution A system at 50° C. for 2 hours, centrifuge for 2 minutes to obtain a precipitate, wash the precipitate, and dry it to obtain material B.
[0021] The present invention also provides the use of the amorphous electrocatalyst Co / MoO2 in the preparation of lithium-sulfur batteries.
[0022] Furthermore, the amorphous electrocatalyst Co / MoO2 is used as positive and negative electrode separators for lithium-sulfur batteries.
[0023] Furthermore, the amorphous electrocatalyst Co / MoO2, carbon black and binder are mixed and ground, N-methylpyrrolidone is added, and the mixture is evenly mixed to obtain a slurry, which is evenly coated on a PP diaphragm by a coating method, and after drying for 12-24 hours, it is used as a positive and negative electrode diaphragm for a lithium-sulfur battery.
[0024] The inventors further studied the mixing of a-Co / MoO2 and carbon nanotubes, and loaded them onto the surface of the substrate film by coating to obtain a-Co / MoO2@PP. On the one hand, the amorphous structure of the material itself can catalyze the redox reaction in the entire region; on the other hand, the polar bonds in the metal oxide MoO2 have chemical adsorption capacity for polysulfides, and can adsorb lithium polysulfides dissolved in the electrolyte, effectively inhibiting the occurrence of the "shuttle effect" and the loss of sulfur elements in the positive electrode. Combining multiple advantages, a lithium-sulfur battery with high capacity retention, good cycle stability, and excellent rate performance was finally obtained.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] In the amorphous electrocatalyst Co / MoO2 provided by the present invention, the strong polarity of the metal oxide enhances the anchoring of polysulfides, effectively inhibits the shuttle effect, reduces the loss of positive electrode sulfur substances, and improves the capacity retention rate. The metal element Co is introduced into the amorphous material to generate a large number of metal bonds, which can effectively improve the inherent low conductivity of the amorphous material and improve the overall conductivity of the catalyst, and has good application prospects in the preparation of positive and negative electrode separators for lithium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The X-ray diffraction pattern of the amorphous electrocatalyst prepared in Example 1 of the present invention;
[0028] Figure 2 This is a scanning transmission electron microscope image of the amorphous structure electrocatalyst prepared in Example 1 of the present invention;
[0029] Figure 3 The discharge specific capacity cycle diagram obtained by applying the electrocatalyst prepared in Example 1 of the present invention to a lithium-sulfur battery after long-term charge and discharge;
[0030] Figure 4 This is a charge-discharge curve diagram obtained when the electrocatalyst prepared in Example 1 of the present invention is applied to a lithium-sulfur battery after long-term charge and discharge. DETAILED DESCRIPTION
[0031] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the figures. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are prepared according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] Example 1: A method for preparing an amorphous electrocatalyst, comprising the following steps:
[0033] The first step is to obtain the precursor material by solvent method:
[0034] Use a measuring cylinder to measure 15 ml of deionized water and put it into a beaker. Add a magnetic rotor and place it on a magnetic stirrer. Set the speed to 300 rpm and keep stirring at this speed throughout the experiment.
[0035] 1.25 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 4H2O) was dissolved in deionized water and stirred continuously until a uniform solution A was obtained;
[0036] Use a pipette to measure 1.78 ml of ethylenediamine monohydrate (CAS No.: 6780-13-8) and dissolve it in the stirring solution A. Stir for 1 minute.
[0037] Weigh 0.0176 g of cobalt acetate tetrahydrate (C4H6CoO4·4H2O) and add it to solution A, and stir for 2 minutes;
[0038] 1M HCl aqueous solution was added dropwise to solution A until precipitation occurred, at which time the pH of the entire system was 4.50;
[0039] The entire solution A system was kept in a water bath at 50°C for 2 hours, and then centrifuged for 2 minutes at a speed of 4000 rpm to collect the precipitate, which was then thoroughly washed with water and ethanol for 3 times, and then dried in an oven at 50°C for 12 hours to obtain material B;
[0040] The second step is to prepare a metal oxide composite amorphous material doped with a single metal by high temperature calcination:
[0041] Material B was placed in a tube furnace as a precursor and calcined at 600°C for 2 hours in an argon atmosphere with a heating rate of 3°C / min. After calcination, the product was collected after cooling to room temperature. The synthesized product is represented as a-Co / MoO2.
[0042] An application of an amorphous electrocatalyst in a lithium-sulfur battery comprises the following steps:
[0043] The prepared materials a-Co / MoO2, carbon black and binder (PVDF) were weighed at a mass ratio of 8:1:1, 0.16 g, 0.02 g and 0.02 g respectively, put into a mortar and grind until they are evenly ground, add N-methylpyrrolidone dropwise into the mortar, mix evenly to obtain a fluid slurry, and use a coating method to evenly coat the slurry on a PP diaphragm. After drying for 12 hours, use it as a lithium-sulfur battery diaphragm material.
[0044] Embodiment 2: A method for preparing an amorphous electrocatalyst comprises the following steps:
[0045] The first step is to obtain the precursor material by solvent method:
[0046] Use a measuring cylinder to measure 15 ml of deionized water and put it into a beaker. Add a magnetic rotor and place it on a magnetic stirrer. Set the speed to 300 rpm and keep stirring at this speed throughout the experiment.
[0047] 2 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 4H2O) was dissolved in deionized water and stirred continuously until a uniform solution A was obtained;
[0048] Use a pipette to measure 1.78 ml of ethylenediamine monohydrate and dissolve it in the stirring solution A. Stir for 1 minute.
[0049] Weigh 0.0176 g of cobalt acetate tetrahydrate (C4H6CoO4·4H2O) and add it to solution A, and stir for 2 minutes;
[0050] 1M HCl aqueous solution was added dropwise to solution A until precipitation occurred, at which time the pH of the entire system was 4.50;
[0051] The entire solution A system was kept in a water bath at 50°C for 2 hours, and then centrifuged for 2 minutes at a speed of 4000 rpm to collect the precipitate, which was then thoroughly washed with water and ethanol for 3 times, and then dried in an oven at 50°C for 12 hours to obtain material B;
[0052] The second step is to prepare a metal oxide composite amorphous material doped with a single metal by high temperature calcination:
[0053] Material B was placed in a tube furnace as a precursor and calcined at 500°C for 2 hours in an argon atmosphere with a heating rate of 3°C / min. After calcination, the product was collected after cooling to room temperature. The synthesized product is represented as a-Co / MoO2.
[0054] An application of an amorphous electrocatalyst in a lithium-sulfur battery comprises the following steps:
[0055] The prepared materials a-Co / MoO2, carbon black and binder (PVDF) were weighed at a mass ratio of 8:1:1, 0.14 g, 0.04 g and 0.04 g respectively, put into a mortar and grind until the grinding is uniform, add N-methylpyrrolidone dropwise into the mortar, mix well to obtain a fluid slurry, and use a coating method to evenly coat the slurry on the PP diaphragm. After drying for 12 hours, it is used as a lithium-sulfur battery diaphragm material.
[0056] Embodiment 3:
[0057] A method for preparing an amorphous electrocatalyst comprises the following steps:
[0058] The first step is to obtain the precursor material by solvent method:
[0059] Use a measuring cylinder to measure 15 ml of deionized water and put it into a beaker. Add a magnetic rotor and place it on a magnetic stirrer. Set the speed to 300 rpm and keep stirring at this speed throughout the experiment.
[0060] 1 g of ammonium molybdate tetrahydrate ((NH4)6Mo7O 24 4H2O) was dissolved in deionized water and stirred continuously until a uniform solution A was obtained;
[0061] Use a pipette to measure 1.78 ml of ethylenediamine monohydrate and dissolve it in the stirring solution A. Stir for 1 minute.
[0062] Weigh 0.0176 g of cobalt acetate tetrahydrate (C4H6CoO4·4H2O) and add it to solution A, and stir for 2 minutes;
[0063] 1M HCl aqueous solution was added dropwise to solution A until precipitation occurred, at which time the pH of the entire system was 4.50;
[0064] The entire solution A system was kept in a water bath at 50°C for 2 hours, and then centrifuged for 2 minutes at a speed of 4000 rpm to collect the precipitate, which was then thoroughly washed with water and ethanol for 3 times, and then dried in an oven at 50°C for 12 hours to obtain material B;
[0065] The second step is to prepare a metal oxide composite amorphous material doped with a single metal by high temperature calcination:
[0066] Material B was placed in a tube furnace as a precursor and calcined at 600°C for 2 hours in an argon atmosphere with a heating rate of 2°C / min. After calcination, the product was collected after cooling to room temperature. The synthesized product is represented as a-Co / MoO2.
[0067] An application of an amorphous electrocatalyst in a lithium-sulfur battery comprises the following steps:
[0068] The prepared materials a-Co / MoO2, carbon black and binder (PVDF) were weighed at a mass ratio of 8:1:1, 0.16 g, 0.02 g and 0.02 g respectively, put into a mortar and grind until they are evenly ground, add N-methylpyrrolidone dropwise into the mortar, mix evenly to obtain a fluid slurry, and use a coating method to evenly coat the slurry on a PP diaphragm. After drying for 12 hours, use it as a lithium-sulfur battery diaphragm material.
[0069] in, Figure 1 and Figure 2They are respectively the X-ray diffraction pattern and the scanning transmission electron microscope image of the amorphous structure electrocatalyst prepared in Example 1 of the present invention. It can be seen from its X-ray diffraction pattern that the crystallization peak position of a-Co / MoO2 is completely consistent with that of standard MoO2 (PDF#32-0671), but the peak intensity is extremely low, indicating that its crystallinity is extremely low, confirming the amorphous phase characteristics of the material. Figure 2 This is a scanning transmission electron microscope image of a-Co / MoO2. It can be seen from the figure that the microstructure of a-Co / MoO2 is a rod-like structure with a flat surface and a large number of tiny channels running through the rod.
[0070] Figure 3 The discharge capacity cycle diagram of the electrocatalyst prepared in Example 1 of the present invention applied to a lithium-sulfur battery after long-term charge and discharge; the processing process is as follows:
[0071] The positive electrode of lithium-sulfur battery is obtained by conventional melt diffusion method;
[0072] a-Co / MoO2, a binder, and carbon black were evenly ground in a ratio of 8:1:1, and coated on a commercial Celgard separator to obtain a positive and negative electrode separator for a lithium-sulfur battery;
[0073] A lithium sheet is used as the negative electrode, and the electrolyte is the electrolyte commonly used in lithium-sulfur batteries;
[0074] The above materials were used to assemble button-type lithium-sulfur batteries, and the cycle stability of the batteries was tested at a rate of 0.2C. After 100 cycles, Figure 3 .Depend on Figure 3 It can be seen that the initial capacity of the battery using the a-Co / MoO2 separator is 1293.70 mAh / g. After 100 cycles, its specific capacity is 969.4 mAh / g, which is 75% of the initial capacity. This proves that the lithium-sulfur battery using the diaphragm of the present invention has good cycle stability and a high capacity retention rate.
[0075] Figure 4 This is a charge-discharge curve diagram obtained when the electrocatalyst prepared in Example 1 of the present invention is applied to a lithium-sulfur battery after long-term charge and discharge. Figure 4 for Figure 3 The charge and discharge curve of the battery cycle is given by Figure 4 It can be seen that after a long cycle, the two discharge platforms (2.3V and 2.1V respectively) of the battery using a-Co / MoO2 separator are still maintained well and the degree of polarization is relatively small.
[0076] The above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. An amorphous electrocatalyst Co / MoO2, characterized in that: The amorphous electrocatalyst Co / MoO2 is prepared as follows: S1. Obtaining precursor materials by solvent method: S11, stirring and dissolving molybdenum salt, ethylenediamine and cobalt salt in water respectively, and then mixing to obtain solution A; S12, adding 1M HCl aqueous solution dropwise to solution A until precipitation occurs; S13, keeping the entire solution A system warm and then centrifuging it to obtain a precipitate, washing the precipitate, and drying it to obtain material B; S2. Preparing a metal oxide composite amorphous material doped with a single metal by high temperature calcination: The material B obtained in step S1 is used as a precursor; in an inert gas atmosphere, the precursor B is calcined at 500-600 degrees Celsius in a tube furnace for 1.5-3 hours, and then the product is collected to obtain the product.
2. The amorphous electrocatalyst Co / MoO2 according to claim 1, characterized in that The molybdenum salt is ammonium molybdate, and the cobalt salt is cobalt acetate tetrahydrate.
3. The amorphous electrocatalyst Co / MoO2 according to claim 2, characterized in that: The concentration ratio of ammonium molybdate, ethylenediamine and cobalt acetate tetrahydrate is (5-8):(10-30):(0.03-0.2).
4. The amorphous electrocatalyst Co / MoO2 according to claim 3, characterized in that The concentration of ammonium molybdate in solution A is 0.05-0.1 g / ml.
5. The amorphous electrocatalyst Co / MoO2 according to claim 1, characterized in that The stirring in step S1 is performed at a rotation speed of 200 to 400 rpm.
6. The amorphous electrocatalyst Co / MoO2 according to claim 1, characterized in that The step S13 is to keep the entire solution A system at 50° C. for 2 hours, centrifuge for 2 minutes to obtain a precipitate, wash the precipitate, and dry it to obtain material B.
7. Use of the amorphous electrocatalyst Co / MoO2 according to claim 1 in the preparation of lithium-sulfur batteries.
8. The use according to claim 7, characterized in that: The amorphous electrocatalyst Co / MoO2 is used as positive and negative electrode separators for lithium-sulfur batteries.
9. The use according to claim 8, characterized in that: The amorphous electrocatalyst Co / MoO2, carbon black and binder are mixed and ground, N-methylpyrrolidone is added, and slurry is obtained after uniform mixing. The slurry is uniformly coated on the PP diaphragm by a coating method, and after drying for 12-24 hours, it is used as the positive and negative electrode diaphragm of the lithium-sulfur battery.